Food raw materials and food production occurrences of deoxynivalenol in different regions. (January 2019) - Wang, Liangliang; Liao, Yuxiao; Peng, Zhao; Chen, Liangkai; Zhang, Wenhao; Nüssler, Andreas K.; Shi, Shaojun; Liu, Liegang; Yang, Wei
Abstract: Background: Deoxynivalenol (DON) is one of the most common mycotoxins in cereal crops and their by-products, posing severe effects to the health of human and animals. However, DON-induced food contamination varies from different regions. Therefore, it is urgent to summarize a review to update information about DON exposure in various food commodities worldwide for future research and regulation. Scope and approach: In this review, we summarize some typical surveys on the occurrence of DON in food raw materials and food production on human DON exposure around the world. In addition, we conclude the findings regarding masked DON in some food and discuss the daily intakes of DON in food from different regions. Key finding and conclusion: DON contamination in food is a serious problem worldwide. Infants and children are susceptible to the high risk of DON exposure, which is harmful to their growth and development. Otherwise, masked DON also represents potential health risks to the population. Last but not least, the study further emphasizes strict and food security policies are needed all over the world. Highlights: DON presented high occurrence and exposure in food worldwide. Masked DON also represented potential health risks to the population. Infants and children were susceptible to the high risk of DON exposure. Strict and food security policies are needed for each country all over the world.